2016
DOI: 10.1080/13811118.2016.1199989
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental Control, Self-Criticism, and Nonsuicidal Self-Injury Among Adolescents: Testing the Reciprocal Relationships by a Three-Wave Cross-Lag Model

Abstract: This study examined the prospective and reciprocal relationships among perceived parental control, self-criticism, and nonsuicidal self-injury (NSSI). We also examined the mediating effect of self-criticism in the relationship between perceived parental control and NSSI. We aimed to find out whether perceived parental control and self-criticism acted as risk factors for NSSI, or consequences of NSSI, or both. A group of 3,600 Chinese adolescents (mean age = 14.63 years, 56.6% female) completed questionnaires, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…Western parents are more respectful of children’s personal choices and self-esteem, whereas Chinese parents tend to emphasize parental authority and more readily supervise their children’s behaviors ( Chao and Tseng, 2002 ). Therefore, Chinese parents employ more monitoring and restriction of their children’s behaviors when adolescents show problem behaviors such as excessive Internet use, whereas Western parents tend to increase parent–child communication, and provide more advice and support in helping their adolescents set rules ( Su et al, 2015 ; You et al, 2017 ). Moreover, Chinese adolescents who grow up in this traditional culture are more likely to accept their parents’ monitoring than are Western adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Western parents are more respectful of children’s personal choices and self-esteem, whereas Chinese parents tend to emphasize parental authority and more readily supervise their children’s behaviors ( Chao and Tseng, 2002 ). Therefore, Chinese parents employ more monitoring and restriction of their children’s behaviors when adolescents show problem behaviors such as excessive Internet use, whereas Western parents tend to increase parent–child communication, and provide more advice and support in helping their adolescents set rules ( Su et al, 2015 ; You et al, 2017 ). Moreover, Chinese adolescents who grow up in this traditional culture are more likely to accept their parents’ monitoring than are Western adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies among western samples (i.e., Belgian and US samples) found that adolescents' engagement in NSSI and other maladaptive behaviors was associated with a perception of a decreased amount of parental control [65,66], while a study among Chinese adolescents showed that engagement in NSSI was associated with an increase in perceived parental control [6]. Researchers explained that this inconsistency may reflect cultural differences in parenting and parent-child relationship [6]. According to Linehan [15], parenting and family environment may also affect one's emotional regulation ability.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Studies using all these scales to examine the relationship between emotional dysregulation and NSSI would be included in the present meta-analyses. relationships [6], self-directed negative emotions (e.g., shame and self-hatred) [7], and even suicide attempts [8,9]. Therefore, understanding the risk factors of NSSI has become an urgent task.…”
Section: Measurement Of Emotional Dysregulationmentioning
confidence: 99%
“…Our findings suggested that an understanding of the conditions whereby someone finds suicide to be a more acceptable action, and his or her levels of mental health status might shed light on the risk of suicide in youth. More specifically, for teachers, school counsellors and social workers alike, intervention programmes such as life education and training as well as cognitive behaviour therapy (Calear et al ; You et al ) may be used to inculcate the value of life and to mitigate the impact of suicidal ideation that resulted from poorer mental health status.
In this sample, we found that the prevalence rate of suicidal ideation was relatively high, which is close to 35.38%. Students with poorer mental health status may have greater suicidal ideation, whereas students with more favourable attitudes towards suicide may have greater suicidal ideation. The detrimental relationship between poorer mental health status and suicidal ideation might be worse when a student's attitudes towards suicide were favourable. This study provides some evidence that students with poorer mental health status might be more likely to report significantly more favourable attitudes towards suicide, which in turn lead to greater suicidal ideation.
…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggested that an understanding of the conditions whereby someone finds suicide to be a more acceptable action, and his or her levels of mental health status might shed light on the risk of suicide in youth. More specifically, for teachers, school counsellors and social workers alike, intervention programmes such as life education and training as well as cognitive behaviour therapy (Calear et al 2016;You et al 2016) may be used to inculcate the value of life and to mitigate the impact of suicidal ideation that resulted from poorer mental health status.…”
Section: Discussionmentioning
confidence: 99%